PENGARUH TINGKAT SUKU BUNGA KREDIT TERHADAP PERMINTAAN KREDIT MODAL KERJA PADA PT. BANK NEGARA INDONESIA (PERSERO) TBK KANTOR CABANG KABUPATEN TORAJA UTARA - Shelin Baby Zhuntania Wijaya; Yohanis L. Ta’dung; Agustinus Mantong (JURNAL ILMIAH EDUNOMIKA, 2025)
The Effect of Credit Interest Rate Levels on Working Capital Credit Demand at PT. Bank Negara Indonesia (Persero) Tbk North Toraja Regency Branch Office. This study aims to determine the Effect of Credit Interest Rate Levels on Working Capital Credit Demand at PT. Bank Negara Indonesia (Persero) Tbk North Toraja Regency Branch Office. The variables of this study are credit interest rates and working capital credit demand. The type of research used in this study is quantitative research. The types of data used in this study are primary data and secondary data. The population in this study is the credit interest rate data report and the working capital credit demand report at PT. Bank Negara Indonesia (Persero) Tbk North Toraja Regency Branch Office, and the sample is the credit interest rate data report and the working capital credit demand report at PT. Bank Negara Indonesia (Persero) Tbk North Toraja Regency Branch Office for the period 2021-2023. The data collection procedures used are documentation and interviews. The data analysis techniques used in this study are simple linear regression tests, coefficient of determination (r2), and partial tests (t-tests). The results of this study indicate that the level of credit interest rates has a negative and significant effect on the demand for working capital credit at PT. Bank Negara Indonesia (Persero) Tbk North Toraja Regency Branch Office. The magnitude of the results obtained from this study, the effect of the level of credit interest rates on the demand for working capital credit at PT. Bank Negara Indonesia (Persero) Tbk North Toraja Regency Branch Office has a significant or important effect. Keywords : Credit Interest Rates, Working Capital Credit Demand